Auditoría de Gestión al Área Administrativa del Ministerio de Desarrollo Urbano y de Vivienda de la Ciudad de Zamora, cantón Zamora, Provincia de Zamora Chinchipe. Periodo: 1 de enero al 31 de diciembre del 2015 - Cango Carpio, Daniela Guadalupe (2017)
The title work on the management audit to the administrative area in the Ministry of Urban Development and Housing of the city of Zamora in the period: January 1 to December 31, 2015, was developed with the purpose of evaluating management subareas Human resources, administrative management, information management and communication to measure the efficiency and effectiveness of activities. In order to meet the first specific objective proposed, internal control questionnaires were applied for each area to be evaluated, and the results of the internal control evaluation were presented, revealing the weaknesses of the institution by weighing each one of the questions Which are included in the questionnaires. In order to develop the second specific objective, information and verification of compliance with the regulations for classification and assessment of posts and annual operational plan were carried out in the Ministry of Urban and Housing Development. The third specific objective was met through the application of indicators of the annual operational plan to measure the efficiency and effectiveness of the activities proposed. The fourth objective was the issuance of a management audit report addressed to the Provincial Director of the Ministry of Urban Development and Housing, providing comments, conclusions and recommendations for the improvement of institutional activities.